Math and Arithmetic
Algebra

# What is the root of the equation m squared -6m -7 equals 0 found by completing the square?

012

###### 2016-02-26 23:16:05

To complete the square for a quadratic ax² + bx + c = 0

1) Divide through by the coefficient of the x² term to get x² + b/a x + c/a = 0; let B = b/a; let C = c/a; the equation is now x² + Bx + c = 0

2) Complete the square by taking half of B and adding it to x and squaring: (x + B/2)²

3) Expanding this gives: (x + B/2)² = x² + Bx + (B/2)² → x² + Bx = (x + B/2)² - (B/2)²

4) Substitute this in the original equation to give: x² + BX + C = (x + B/2)² - (B/2)² + C

5) This can now be solved as (x + B/2)² - (B/2)² + C = 0 → (x + B/2)² = (B/2)² - C

For m² - 6m - 7 = 0, completing the square gives:

(m - 6/2)² - (6/2)² - 7 = 0

→ (m - 3)² - 9 - 7 = 0

→ (m - 3)² -16 = 0

→ (m - 3)² = 16

→ m - 3 = ±4

→ m = 3 ± 4

→ m = 7 or -1.

๐ฆ
0
๐คจ
0
๐ฎ
0
๐
0

###### 2016-02-21 19:49:34

The coefficient of m is -6 so you need to use -6/2 = -3 for completing the squares.

m^2 - 6m - 70

=> m^2 - 6m = 70

=> (m - 3)^2 = 70 + (-3)^2 = 70 + 9

=> (m - 3)^2 = 79

=> m - 3 = +/- sqrt(79)

=> m = 3 +/- sqrt(79)

๐ฆ
0
๐คจ
0
๐ฎ
0
๐
0

###### 2016-02-24 16:59:28

I think you want: m² - 6m - 70 = 0. Complete the square, so if you have something like
(x - A)², then you will get x² - 2Ax + A². So let's look at it. The coefficient of x is -6, so if -6x equates to -2Ax, then A must be 3.

So we have (m - 3)² = m² - 6m + 9, except you have m² - 6m - 70, so to get it like that we can do this: m² - 6m + 9 - 79 will equal your expression (9 - 79 = -70).

m² - 6m + 9 - 79 = 0. Add 79 to both sides. m² - 6m + 9 = 79

Now remember that m² - 6m + 9 = (m - 3)², so we have (m - 3)² = 79.

Square root of both sides: m - 3 = sqrt(79) and also: m - 3 = -sqrt(79).

Add 3 to both sides: m = 3 + sqrt(79) and m = 3 - sqrt(79)

๐ฆ
0
๐คจ
0
๐ฎ
0
๐
0

## Related Questions

It cannot be solved because the discriminant of the quadratic equation is less than zero

You are describing a circle, with its center at the origin and a radius of 4 (the square root of 16)

If you mean: 11x2-34x+3 = 0 then the solutions are x = 1/11 and x = 3 by completing the square or using the quadratic equation formula

Since a squared plus b squared equals c squared, that is the same as c equals the square root of a squared plus b squared. This can be taken into squaring and square roots to infinity and still equal c, as long as there is the same number of squaring and square roots in the problem. Since this question asks for a and b squared three times, and also three square roots of a and b both, they equal c. Basically, they cancel each other out.

Completing the square is one method for solving a quadratic equation. A quadratic equation can also be solved by several methods including factoring, graphing, using the square roots or the quadratic formula. Completing the square will always work when solving quadratic equations and is a good tool to have. Solving a quadratic equation by completing the square is used in a lot of word problems.I want you to follow the related link that explains the concept of completing the square clearly and gives some examples. that video is from brightstorm.

Without an "equals" somewhere along the way, you only have an expression, not an equation.Without an equation, there is no question, and nothing to answer.

a squared plus b squared equals c squared.example: a=5 5sq is 25 b=8 bsq is 64 64+25 or a squared + b squared=89. then you find the square root of 89 and there's your answer. 9.4 [rounded]

By using the quadratic equation formula or by completing the square

x equals negative b plus or minus the square root of b squared minus 4bc over 2a

The number than when squared equals 110 is the square root of 110 = &plusmn;10.488 (3dp)

Equation: x^2 +y^2 -4x -2y -4 = 0 Completing the squares: (x-2)^2 +(y-1)^2 -4-1-4 = 0 So: (x-2)^2 +(y-1)^2 = 9 Therefore the centre of the circle is at (2, 1) and its radius is 3

This quadratic equation has no solutions because the discriminant is less than zero.

Square root of x = 29 can be rearranged by squaring both sides of the equation. That would leave you with: x = 29^2 (or 29 squared) So, work out what 29 squared is and that's what x is equal to.

it's called the formula for an area A=LW (area for a rectangle) (area equals length times width) A=S2 (area for a square) (area equals side squared)

There are 10mm in 1cm. Therefore there are 102mm2 in 1cm2 which equals 100 square millimetres.

a number multiplied by itself equals the square number. Example; 4 x 4 = 16 4 square equals 16. 16 is the squared number.

Yes, the same.I have different takeExample:4 square miles--- equals 2 miles by 2 miles- equals 2 mi, squared.4 miles squared- equals 16 square miles---- equals 4 mi. per side.

###### Math and ArithmeticAlgebraPythagorasAreaGeometryHome & GardenScienceMicrosoft Windows

Copyright ยฉ 2020 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.